Association between obesity and history of atopy with atopic dermatitis in children: A cross-sectional study - Batan, Putu Nila Wardhani; Ariana, Ariana; Wardhana, Made (UI Scholars Hub, 2019)
Background: The prevalence of atopic dermatitis (AD) has rapidly increased in the past 4 decades and has been mostly observed in children. The prevalence of obesity has also significantly increased worldwide, suggesting that the two conditions may be associated. Methods: This retrospective analytic study involved a cross-sectional design and used secondary data taken from the medical record of patients who visited the Pediatric Dermatology Subdivision at Dermatology and Venereology Polyclinic Sanglah General Hospital from January 2015 to December 2015. Thirty-two samples were selected. Results: The prevalence ratio of obesity among subjects with AD was 2.178 (95% CI = 1.034–4.587; p < 0.05), which indicated a significant association between obesity and AD. This study also found a significant association between the history of atopy and AD, and the prevalence ratio was 2.566 (95% CI = 1.099–5.990; p < 0.05). The risk of developing AD among children with obesity was higher than that among children without obesity. Conclusion: Obesity and history of atopy were significantly associated with AD in children.